Influence of Alumina Addition on the Optical Properties and the Thermal Stability of Titania Thin Films and Inverse Opals Produced by Atomic Layer Deposition - Waleczek, Martin (Nanomaterials (Basel), 2021)
TiO(2) thin films deposited by atomic layer deposition (ALD) at low temperatures (<100 °C) are, in general, amorphous and exhibit a smaller refractive index in comparison to their crystalline counterparts. Nonetheless, low-temperature ALD is needed when the substrates or templates are based on polymeric materials, as the deposition has to be performed below their glass transition or melting temperatures. This is the case for photonic crystals generated via ALD infiltration of self-assembled polystyrene templates. When heated up, crystal phase transformations take place in the thin films or photonic structures, and the accompanying volume reduction as well as the burn-out of residual impurities can lead to mechanical instability. The introduction of cation doping (e.g., Al or Nb) in bulk TiO(2) parts is known to alter phase transitions and to stabilize crystalline phases. In this work, we have developed low-temperature ALD super-cycles to introduce Al(2)O(3) into TiO(2) thin films and photonic crystals. The aluminum oxide content was adjusted by varying the TiO(2):Al(2)O(3) internal loop ratio within the ALD super-cycle. Both thin films and inverse opal photonic crystal structures were subjected to thermal treatments ranging from 200 to 1200 °C and were characterized by in- and ex-situ X-ray diffraction, spectroscopic ellipsometry, and spectroscopic reflectance measurements. The results show that the introduction of alumina affects the crystallization and phase transition temperatures of titania as well as the optical properties of the inverse opal photonic crystals (iPhC). The thermal stability of the titania iPhCs was increased by the alumina introduction, maintaining their photonic bandgap even after heat treatment at 900 °C and outperforming the pure titania, with the best results being achieved with the super-cycles corresponding to an estimated alumina content of 26 wt.%.